Experimental research on the development of rutting in asphalt concrete pavements reinforced with geosynthetic materials - Laurinavičius, Alfredas; Oginskas, Rolandas (Journal of Civil Engineering and Management, 2006)
The article sets out to explore reasons for the development of shear strains and rutting in asphalt pavement as well as to suggest and describe the main methods for reducing the deformation. The impact of geosynthetic materials is defined through reological characteristics of asphalt: the modulus of elasticity and the viscosity of asphalt. The research has been conducted on the experimental road section in the city of Vilnius. The measurements have been based on the plate‐bearing test. Sustaining the measurements results is defining the dependency of geosynthetics materials on the depth of rutting and the modulus of elasticity of asphalt concrete. The paper also includes regression equations which show the interdependence of the modulus of elasticity of asphalt concrete and the depth of rutting. Eksperimentiniai provėžų atsiradimo ir vystymosi tyrimai asfaltbetonio dangose, armuotose geosintetinėmis medžiagomis Santrauka. Išnagrinėtos pagrindinės šlyties deformacijų ir provėžų asfaltbetonio dangose susidarymo priežastys bei pagrindiniai būdai šioms deformacijoms mažinti. Geosintetinių medžiagų įtaka šioms deformacijoms nagrinėjama remiantis reologinėmis asfaltbetonio charakteristikomis: asfaltbetonio tampros moduliu ir asfaltbetonio klampumu. Geosintetinėmis medžiagomis armuotų asfaltbetonio dangų tyrimai atlikti eksperimentiniame bandymų ruože, Vilniaus mieste, naudojant statinį bandymo štampą. Remiantis gautais tyrimų rezultatais išvestos priklausomybės, kaip provėžų gylį lemia geosintetinės medžiagos, ir asfaltbetonio tampros modulis. Šiame straipsnyje pateiktos regresinės priklausomybės, atspindinčios, kaip provėžų gylis priklauso nuo asfaltbetonio tampros modulio. Reikšminiai žodžiai: asfaltbetonis, asfaltbetonio armavimas, geosintetinės medžiagos, asfaltbetonio tampros modulis, provėžų gylis. First Published Online: 14 Oct 2010